The Assassination of Christopher Marlowe (A New View) - Tannenbaum, Samuel A. (Samuel Aaron), 1874?-1948 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Assassination of Christopher Marlowe (A New View)" by Samuel A. Tannenbaum is a historical account published in the late 1920s. This book explores the mysterious events surrounding the assassination of the renowned Elizabethan playwright Christopher Marlowe, delving into the political and social contexts of his time. Tannenbaum presents a new interpretation of Marlowe's death, proposing that it was not merely a tragic accident but rather a calculated murder tied to the intrigues of the Elizabethan court. In this compelling work, Tannenbaum investigates the circumstances leading to Marlowe$1 (Bs death on May 30, 1593, alongside the arrest of fellow playwright Thomas Kyd, who accused Marlowe of heresy and blasphemy while being tortured. Through a detailed examination of contemporary documents and accounts, the author argues that political machinations involving powerful figures, including Sir Walter Raleigh, motivated the assassination. Tannenbaum presents evidence suggesting that Marlowe's death was orchestrated to silence him, particularly in light of threats he posed to influential nobility due to his knowledge of state secrets. The book unfolds a narrative filled with tension, revealing the interplay between art, politics, and betrayal in the tumultuous world of Elizabethan England. (This is an automatically generated summary.)s
Release date is 2021-06-07
E-text prepared by Tim Lindell, Graeme Mackreth, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images digitized by the Google Books Library Project (https://books.google.com) and generously made available by HathiTrust Digital Library (https://www.hathitrust.org/)
Keywords: Raleigh, Walter, Sir, 1552?-1618; Marlowe, Christopher, 1564-1593 -- Death and burial; Assassination -- England -- History -- 16th century